Effect of surface sealant on the color stability and whiteness index of single-shade resin composites after staining and bleaching - Muhammet Fidan; Özhan Yağcı (Restorative Dentistry & Endodontics)
ObjectivesThe aim of the current study was to evaluate the effect of polishing systems and surface sealant on the color stability and whiteness index of single-shade resin composites after staining and bleaching.Materials and MethodsThree single-shade (Omnichroma, Charisma Diamond One, Zenchroma) and one multi-shade (Filtek Z250) materials were tested. From each resin composite, 40 specimens were prepared. The specimens were divided into 4 subgroups (n = 10) according to the surface treatments: 1-step polishing, 1-step + Biscover LV, 2-step polishing, and 2-step polishing + Biscover LV. Color differences (ΔE00) were calculated after being immersed in the coffee solution for 12 days. After the staining, the specimens were immersed in a whitening mouthrinse (Crest-3D White) for 12 hours. Whiteness index differences (∆WID = WID after staining − WID after bleaching) values were recorded. The generalized linear model was used for analysis (p < 0.05).ResultsThe lowest and highest ΔE00 values were found for Zenchroma and Charisma Diamond One respectively. Sealed groups indicated higher ΔE00 values than nonsealed groups with significant differences (p = 0.008). The lowest and highest ΔWID values were found for Zenchroma and Charisma Diamond One respectively. Sealed groups indicated lower ΔWID values than nonsealed groups with significant differences (p = 0.022).ConclusionsThe use of surface sealant increased the discoloration and showed less whiteness change in resin materials. When the 1-step was compared with the 2-step polishing, the effects on the color stability and whiteness index values of the resin materials were similar.